Strategi Siaran Kolaborasi Radio Dakwah MQ FM Subang dalam Meningkatkan Atensi Pendengar - Wahyuni, Ayu Sri; Muhlis, Atjep; Nur Chidayah, Prita Priantini (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2024)
This research aims to explore the communication planner strategies, broadcast messages, and target audience of Radio Dakwah MQ FM Subang in enhancing listener attention. The research method employed descriptive method with a qualitative approach. The research theory utilized in this study is the Computer Mediated Communication (CMC) theory. The research findings indicate that the communication planner strategies of Radio MQ FM Subang to enhance listener attention consist of three aspects. Firstly, in the communicator planning, the focus is on determining the broadcaster, the broadcaster's communication approach to the listeners, and building closeness with the audience. Secondly, in message planning, the strategies include message selection and composition, presenting engaging information, and ensuring messages can influence the listeners. Thirdly, in audience targeting planning, there is demographic and psychographic analysis as well as providing broadcasts through online streaming.